Un enfoque diferente para las políticas europeas de inmigración. A different focus for european immigration policies - Pariza Castaños, Luis Miguel (Papeles del Este, 2006)
The author’s starting point is that the European Union lacks a common policy on immigration and political asylum, in spite of such a policy first having been proposed five years ago. The author argues that migrations should be viewed as something that have always existed during humankind’s history and should be seen as a means to avoid the dangers of an increasingly aged Europe, namely, a serious threat to its system of pensions and a clear comparative disadvantage with respect to the Unites States. Until now country-by-country regulation and overwrought and ungenerous immigration procedures have translated into a failure that has produced an underground economy, social and labour dumping. This is evident with each successive amnesty granted. There is no indication the flow of irregular immigrants is going to decrease. This state of affairs will only change when the European Union possesses a “global and horizontal” legal framework that marks a pattern for European governments to follow and when the Council of Europe abandons the rule of unanimity and begins to adopt co-decision procedures with the Parliament.